Low-input redoxomics facilitates global identification of metabolic regulators of oxidative stress in the gut - Xina Xiao; Meng Hu; Li Gao; Huan Yuan; Baochen Chong; Yu Liu; Rou Zhang; Yanqiu Gong; Dan Du; Yong Zhang; Hao Yang; Xiaohui Liu; et al. (Signal Transduction and Targeted Therapy)
Abstract Oxidative stress plays a crucial role in organ aging and related diseases, yet the endogenous regulators involved remain largely unknown. This work highlights the importance of metabolic homeostasis in protecting against oxidative stress in the large intestine. By developing a low-input and user-friendly pipeline for the simultaneous profiling of five distinct cysteine (Cys) states, including free SH, total Cys oxidation (Sto), sulfenic acid (SOH), S-nitrosylation (SNO), and S-glutathionylation (SSG), we shed light on Cys redox modification stoichiometries and signaling with regional resolution in the aging gut of monkeys. Notably, the proteins modified by SOH and SSG were associated primarily with cell adhesion. In contrast, SNO-modified proteins were involved in immunity. Interestingly, we observed that the Sto levels ranged from 0.97% to 99.88%, exhibiting two distinct peaks and increasing with age. Crosstalk analysis revealed numerous age-related metabolites potentially involved in modulating oxidative stress and Cys modifications. Notably, we elucidated the role of fumarate in alleviating intestinal oxidative stress in a dextran sulfate sodium (DSS)-induced colitis mouse model. Our findings showed that fumarate treatment promotes the recovery of several cell types, signaling pathways, and genes involved in oxidative stress regulation. Calorie restriction (CR) is a known strategy for alleviating oxidative stress. Two-month CR intervention led to the recovery of many antioxidative metabolites and reshaped the Cys redoxome. This work decodes the complexities of redoxomics during the gut aging of non-human primates and identifies key metabolic regulators of oxidative stress and redox signaling.